Performance evaluation of micro bubble generator on physiological response of Nile tilapia Oreochromis niloticus (Linnaeus, 1758) farmed at different densities in recirculating aquaculture system - Sri Wahyuni Firman; Kukuh Nirmala; Eddy Supriyono; Nurul Taufiqu Taufiqu Rochman (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2019)
Micro-bubble generator is a device to maintain water quality by producing micron-sized bubbles. This study aims to evaluate the application of micro-bubble generator in different density on production performance and physiological response of nile tilapia reared in recirculating system. An experiment was designated by performing 3 densities, namely 15 , 30, and 45 individuals 60 L-1 with 3 replications. Every single unit of experiment applies a 34×42×41 cm3 maintenance container. The length size of fish used in this study was 7.44±2.89 cm and body weight of 10,96 ± 0,53 g. Fish were reared for 42 days in recirculation water system and fed ad satiation. The results of the evaluation of the physiological response showed that fish kept at density up to 45 60 L-1 did not show any changes, indicating that fish was in stress condition. The best production performance was in treatment A (15 individuals 60 L-1) with a specific growth rate of 1.87 ± 0.15% and a feed conversion ratio of 0.95 ± 0.08. Abstrak Pembangkit gelembung mikro merupakan suatu alat yang dapat menghasilkan gelembung udara berukuran mikro. Penelitian ini bertujuan untuk mengevaluasi penggunaan pembangkit gelembung mikro pada kepadatan yang berbeda terhadap performa produksi dan respons fisiologis ikan nila yang dipelihara dalam sistem resirkulasi. Penelitian ini dilakukan dengan metode eksperimental dengan tiga perlakuan kepadatan yaitu 15 ekor, 30 ekor dan 45 ekor 60 L-1 yang diulang sebanyak tiga kali. Wadah pemeliharaan berukuran 34×42×41 cm3. Ukuran ikan yang digunakan dalam penelitian ini memiliki panjang 7,44±2,89 cm, serta bobot 10,96±0,53 g. Aplikasi pembangkit gelembung mikro dibe-rikan pada awal hingga akhir pemeliharaan selama 42 hari dengan sistem resirkulasi dan ikan diberi pakan secara ad satiation. Hasil evaluasi terhadap respons fisiologis menunjukkan bahwa ikan yang dipelihara hingga kepadatan 45 ekor 60 L-1 tidak menunjukkan adanya perubahan yang mengindikasikan ikan mengalami stress. Performa produksi terbaik adalah pada perlakuan A (15 ekor 60 L-1) dengan laju pertumbuhan spesifik 1,87±0,15% dan nisbah konversi pakan 0,95±0,08.